2017
DOI: 10.1021/acsami.7b15612
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright Fluorescent Silica Nanoparticles Embedded with Conjugated Oligomers and Their Application in Latent Fingerprint Detection

Abstract: Fluorescent micro- and nanosized particles have a broad range of applications in biology, medicine, and engineering. For these uses, the materials should have high emission efficiency and good photostability. However, many organic fluorophores suffer from aggregation-induced quenching effects and photobleaching. Here, we used a simple method based on covalently blending a fluorescent conjugated oligomer with silica nanoparticles to achieve emission quantum yields as high as 97%. The resulting system also showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 65 publications
1
47
0
1
Order By: Relevance
“…Upon comparison with conventional powders, the NPs gave sharp ridges and low background. Zhang et al reported the synthesis of optically stable blue‐emitting conjugated oligofluorene incorporated SiO 2 NPs (OF/SiO 2 ) having a 97% quantum yield (S. Zhang et al, ). The authors compared the efficiency of these OF/SiO 2 (51 nm diameter) with the SiO 2 NPs synthesized by the Stöber (66 nm) and microemulsion methods (123 nm) and found that, although all three NPs developed good ridge detail, the best results were achieved by the OF/SiO 2 NPs followed by those produced using the Stöber and microemulsion methods.…”
Section: Silica Npsmentioning
confidence: 99%
“…Upon comparison with conventional powders, the NPs gave sharp ridges and low background. Zhang et al reported the synthesis of optically stable blue‐emitting conjugated oligofluorene incorporated SiO 2 NPs (OF/SiO 2 ) having a 97% quantum yield (S. Zhang et al, ). The authors compared the efficiency of these OF/SiO 2 (51 nm diameter) with the SiO 2 NPs synthesized by the Stöber (66 nm) and microemulsion methods (123 nm) and found that, although all three NPs developed good ridge detail, the best results were achieved by the OF/SiO 2 NPs followed by those produced using the Stöber and microemulsion methods.…”
Section: Silica Npsmentioning
confidence: 99%
“…On the other hand, luminescent nanosized powders excitable at higher wavelengths is certainly advantageous for developing LFPs at relatively cheaper processing cost. As an effort, Zhang et al synthesize silica nanoparticles of size ≈66 nm with organic based conjugated oligomer showing excellent fluorescence and photostability after exciting with UV light of 365 nm . Recently, Kumbhakar et al demonstrate tuning of photoluminescence (PL) emissions of 2D ZnS nanosheets after Mn and Cu codoping for detecting LFPs under excitation of 365 nm UV light .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, analytes can be detected by monitoring changes in the fluorescence of the materials. To achieve high detection reliability and sensitivity, great efforts have been devoted to preparing novel fluorescent materials with high quantum yields and good photostability, including organic molecules and inorganic nanoparticles . Among such fluorescent materials, fluorescent organic molecules are particularly safe for use in biological applications .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high detection reliability and sensitivity, great efforts have been devoted to preparing novel fluorescent materials with high quantum yields and good photostability, including organic molecules and inorganic nanoparticles. [8][9][10][11] Among such fluorescent materials, fluorescent organic molecules are particularly safe for use in biological applications. [12] The energy levels of organic molecules are mainly determined by their chemical structures and are less dependent on their size, unlike inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%